Practical Application of Time-Motion Analysis of Judo Female Cadets’ Combats Between Weight Divisions - Aedo-Munoz, E (Routledge, 2020)
The purpose of the study was to compare the female cadet`s judo weight divisions based on time-motion analysis. For this, participants were grouped by weight, according to the following criteria: Lighters (n = 32, ≤ 48 kg), Middlers (n = 24, > 48 kg and  ≤ 63 kg) and Heavies (n = 14, > 63 kg) of four local judo championships. Time-motion analysis were observed, according to each combat phase (i.e. combat, standing combat, approach, gripping, attack, groundwork combat and pause phases). ANOVA and Bonferroni tests were used, p ≤.05. The results indicated differences between total combat phase, with heavies (109.6 ± 67.2 s) <lighters (233.8 ± 163.4 s) and middlers (228.0 ± 1119.8 s), total standing combat, with heavies (58.3 ± 29.9 s) <lighters (106.4 ± 66 s), approach phase, with heavies (21.3 ± 10.6 s) <lighters (44.3 ± 33.5 s) and groundwork phase, with middlers (71.3 ± 43.8 s) > lighters (41.2 ± 25 s) and heavies (31.4 ± 27.7 s). In conclusion, female cadet training programmes should be adjusted according to their weight divisions with consideration for the temporal structure of the competitive environment. © 2020, © 2020 Cardiff Metropolitan University.